General guideline for marketing plan (Part 1) - Ismail, Irwan; Mohamed Ahmad, Ferozah Haini; Nik Jaafar, Nik Fazlin Hiryati; Nik Hassan, Nik Fakrulhazri; Ibrahim, Norlaila (Universiti Teknologi MARA, Terengganu, 2021)
The marketing aspect is very important not only to existing enterprises but especially to new ventures. This plan will detail out among others; the 4Ps of the marketing mix. In completing a business plan, this section will be the starting point. Hence, you must make sure the information and figures developed are accurate and relevant.